Human-Tech Symbiosis: Collaboration between Managers and AI Systems in Strategic Decision Making - Eliagus Telaumbanua; Sauca Ananda Pranidana; Rustiyana Rustiyana (PT. Anagata Sembagi Education, 2025)
Digital transformation has shifted the paradigm of strategic decision-making from intuition-based judgment toward a collaborative model that integrates human intelligence with artificial intelligence (AI). AI serves as an analytical engine that processes large-scale data and generates predictive recommendations, while managers retain interpretive authority regarding organizational context, strategic intent, and ethical implications. This study aims to explore how collaboration between managers and AI systems forms human–tech symbiosis in strategic decision-making. A qualitative method with thematic literature analysis was applied following the interpretive framework of Creswell and Poth (2018). Findings reveal that AI enhances decision effectiveness by improving analytical accuracy, speeding information processing, and reducing cognitive bias; however, these benefits become optimal only when accompanied by managerial trust, algorithmic transparency, and human control over final decision outcomes. The study confirms that the most effective strategic decisions emerge not from the dominance of either AI or human intuition but from the symbiotic combination of computational reasoning and human strategic reflection. It concludes that organizations must develop human–AI capability simultaneously, rather than merely adopting AI systems, to achieve more adaptive, accurate, and sustainable strategic decision-making.